Preparation method of recycled polypropylene / polyolefin elastomer / carbon fiber composite material

The preparation and recovery of polypropylene/polyolefin elastomer/carbon fiber composite materials were solved by mechanical blending, which solved the problem of POE improving PP toughness but reducing mechanical strength, and achieved high mechanical properties, thermal stability and impact strength of the composite materials.

CN119704457APending Publication Date: 2025-03-28XINJIANG UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411874072.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, although polyolefin elastomer (POE) can improve the toughness of polypropylene (PP) substrates, it often leads to a decrease in mechanical strength.

Method used

The mechanical blending method is used to prepare and recovered polypropylene/polyolefin elastomer/carbon fiber composite materials, and ensure uniform mixing and molding of the materials through shaking, twin screw extrusion, crushing and granulation, vacuum drying, twin screw injection molding and standstilling.

Benefits of technology

The excellent mechanical properties, thermal stability and impact strength of composite materials are achieved, and the overall strength and application prospects of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119704457A_ABST
    Figure CN119704457A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of composite materials, and provides a preparation method of a recycled polypropylene / polyolefin elastomer / carbon fiber composite material, which comprises the following steps: S1, shaking R-PP, POE and CF; s2, mixing the R-PP, the POE and the CF by using a double-screw extruder so as to ensure that the materials are uniformly mixed; s3, feeding the mixed material into a crusher for crushing and granulating to obtain a granular material; s4, drying the granular material in a vacuum dryer to remove moisture in the material; s5, molding the dried granular material by using a double-screw injection molding machine; s6, after injection molding is completed, the prepared composite material is placed at the room temperature, standing is conducted for 36-48 hours, and internal stress is eliminated; the carbon fiber reinforced polyolefin elastomer / regenerated polypropylene composite material prepared by a mechanical blending method has excellent mechanical properties, thermal stability and impact strength, and provides potential application prospects and development directions for the field of material application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite materials, in particular to a preparation method of recycled polypropylene / polyolefin elastomer / carbon fiber composite materials. Background Art

[0002] Polypropylene (PP) has high mechanical strength and good processing properties and is widely used in food and pharmaceutical packaging. Polyolefin elastomer (POE) is a commonly used reinforcing phase to enhance the toughness of resins. POE provides mechanical support and fluidity for composite materials due to its molecular structure containing long flexible chains and short branches. Carbon fiber (CF) is a commonly used comprehensive modification for composite materials.

[0003] At present, there is still considerable room for exploration of the interrelationships during the processing of multi-component blends and the stable dispersion between multiphase systems: although POE can effectively improve the toughness of the PP substrate, it often leads to a decrease in mechanical strength.

[0004] To this end, those skilled in the art have proposed a method for preparing a recycled polypropylene / polyolefin elastomer / carbon fiber composite material to solve the problems raised in the background art. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a preparation method of recycled polypropylene / polyolefin elastomer / carbon fiber composite materials to solve the problem that POE in the prior art can effectively improve the toughness of the PP substrate but often leads to a decrease in mechanical strength.

[0006] A method for preparing a recycled polypropylene / polyolefin elastomer / carbon fiber composite material comprises the following steps:

[0007] S1, shaking R-PP, POE, and CF;

[0008] S2, mixing R-PP, POE and CF using a twin-screw extruder to ensure uniform mixing of the materials;

[0009] S3, sending the mixed materials into a crusher for crushing and granulation to obtain granular materials;

[0010] S4, placing the granular material in a vacuum dryer for drying to remove moisture from the material;

[0011] S5, molding the dried granular material using a twin-screw injection molding machine;

[0012] S6, after the injection molding is completed, the prepared composite material is placed at room temperature for 36 to 48 hours to eliminate internal stress.

[0013] Preferably, in step S1, the temperature of R-PP, POE and CF is between 175°C and 180°C.

[0014] Preferably, in step S4, drying is performed at a temperature of 80° C. for 8 hours.

[0015] An application of recycled polypropylene / polyolefin elastomer / carbon fiber composite material in pipes and disposable water cups.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. The carbon fiber reinforced polyolefin elastomer / recycled polypropylene composite material prepared by the mechanical blending method of the present invention has excellent mechanical properties, thermal stability and impact strength, and provides potential application prospects and development directions for the field of material application. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the overall structure of the present invention;

[0019] Figure 2 are different chemical bond vibration peaks of the composite material of the present invention;

[0020] Figure 3 It is the scanning result of XRD of the composite material of the present invention;

[0021] Figure 4 Thermodynamic analysis of the composite material of the present invention;

[0022] Figure 5 (a) is the result of the density of the composite material of the present invention;

[0023] Figure 5 (b) is the relationship between the POE content and the overall strength of the composite material of the present invention;

[0024] Figure 5 (c) is the bending property of the composite material C of the present invention;

[0025] Figure 5 (d) is the impact strength of composite material A;

[0026] Figure 5 (e) is the impact strength of composite material B;

[0027] Figure 5 (f) is the impact strength of composite material C;

[0028] Figure 6 The scanning electron microscope images of the A0, C1 and C5 fracture surfaces of the composite material of the present invention at different magnifications are shown. DETAILED DESCRIPTION

[0029] The following embodiments of the present invention are described in further detail in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0030] Embodiment 1:

[0031]

[0032]

[0033] As attached Figure 1 As shown, the preparation of recycled polypropylene / polyolefin elastomer / carbon fiber composite material according to the above table includes the following steps:

[0034] S1, shaking R-PP, POE and CF, the temperature of R-PP, POE and CF is between 175℃-180℃;

[0035] S2, using a twin-screw extruder to mix R-PP, POE and CF to ensure uniform mixing of the materials;

[0036] S3, sending the mixed materials into a crusher for crushing and granulation to obtain granular materials;

[0037] S4, placing the granular material in a vacuum dryer and drying it at 80° C. for 8 hours to remove moisture from the material;

[0038] S5, molding the dried granular material using a twin-screw injection molding machine;

[0039] S6, after the injection molding is completed, the prepared composite material is placed at room temperature for 36 to 48 hours to eliminate internal stress.

[0040] An application of recycled polypropylene / polyolefin elastomer / carbon fiber composite material in pipes and disposable water cups.

[0041] The R-PP and PP grafted maleic anhydride (PP-g-MAH) in this experimental scheme were purchased from Dongguan Hongxing New Materials Co., Ltd., and POE was purchased from Suzhou Yinglun Er Engineering Plastics Co., Ltd. In order to improve the overall strength of the material, micron-sized carbon fiber powder purchased from Carbon Technology (Shenzhen) Co., Ltd. was used.

[0042] Measure with a density meter, reset the liquid level before measuring, and measure at least 5 samples.

[0043] After eliminating the internal stress, the tensile test, bending test and notch impact test were carried out, and the average value of the results of 5 samples was taken to ensure the reliability of the data. The sample size for the tensile test was 80mm×13mm×2mm. The sample size for the bending test was 65mm×13mm×5mm, and the sample size for the impact test was 80mm×10mm×4mm.

[0044] The microstructure of the composite material was studied using a German Zeiss Sigma 300 scanning electron microscope (instrument grade). Due to the poor conductivity of the R-PP substrate, a gold spraying method was used to obtain a clear image, mainly studying the microstructure and dispersion state of the multiphase structure and interphase structure.

[0045] The melting and crystallization behavior of R-PP / POE / CF blends after adding PP-g-MAH phase solvent was studied by TA DSC250 (USA) in a protective atmosphere (nitrogen). The method was to increase the temperature to 350°C, then reduce the temperature, and increase the temperature again, using the same temperature rise and fall rate (10°C / min). The crystallization rate was calculated using the following formula:

[0046]

[0047] Where ΔH m is the melting enthalpy of the sample (J / g), represents the melting enthalpy of 100% crystalline PP, Indicates the R-PP content in the sample.

[0048] To examine the composition of the blends, thermogravimetric analysis (TGA) was performed using a Netzsch TG 209F3 Tarsus from Germany under a protective nitrogen atmosphere. Approximately 6 mg of sample was placed in a ceramic crucible and heated from room temperature to 800 °C at a rate of 10 °C / min.

[0049] Fourier transform infrared (FT-IR) spectroscopy was performed using a Vertex 70 RAMI technology. Spectra were collected at a resolution of 16 cm-1 in the wavelength range of 4000 cm-1–400 cm-1. The plastic products were cut into powder and compressed with potassium bromide, weighing approximately 5 mg.

[0050] The test was carried out using a Bruker D8 from Germany, using a solid sample cut from a copper target, with a scanning range of 5°-90° and a specific scanning temperature of 2° / min.

[0051] As attached Figure 2 As shown, Figure 2Different chemical bond vibration peaks of the composites are shown. The chemical structure and interaction of the composites were analyzed by Fourier transform infrared spectroscopy (FT-IR) to ensure the accuracy of their composition. The infrared results fully prove that the base material of the C system is R-PP, because it contains many iconic analytical information: mainly including -CH3 asymmetric stretching vibration peak at 2956cm-1, -CH2 asymmetric stretching vibration at 2918cm-1, -CH2 symmetric stretching vibration at 2842cm-1, -CH2 bending vibration representative size at 1457cm-1, -CH3 bending vibration representative size at 1377cm-1, and -CH3 swing vibration at 1166cm-1, -CH2 rocking vibration at 718cm-1. These peaks indicate the presence of methyl and methylene groups in the chemical structure of R-PP. In addition, R-PP also shows more complex infrared peak signals than ordinary PP, which may be closely related to its own blend recovery rate. For R-PP based blends or composites, its attribution by IR spectroscopy should be the most critical step to determine the significance of the substrate from uncertain origin.

[0052] As attached Figure 3 As shown, Figure 3The XRD scan results are shown, which are usually used to observe crystal peaks or determine the chemical structure of polymers. Although the infrared results speculate that the results of the matrix may be R-PP, in order to confirm its crystal structure, this needs to be explained by XRD. The curve shows that both A0 and C series samples have peaks near 14.1°, 16.9° and 21.4°, belonging to the (110), (040) and (131) crystal planes, respectively. Continuing to speculate that A0 and C series may belong to α-PP, XRD tests show that there is no β-PP crystal configuration in the A0 and C systems, and α-PP is the most stable and classic PP crystal form. At this time, combined with infrared analysis, it can be concluded that A0 and C series are indeed PP substrate materials, and the appearance of impurity peaks is 29.3° (sharp peak), which confirms that the R-PP material is similar to what we expected and is self-blended. R-PP is obtained by multiple mixing of crushed and recycled materials based on PP or PP. Waste polymers mainly based on R-PP often have performance defects during the initial processing. Due to direct production, there are no process restrictions such as stretching and extrusion during processing, and the recycled materials produced have extremely poor crystalline phases, which is usually attributed to amorphous crystallization or impurity nucleation. Therefore, although the crystallinity has been improved to varying degrees, the overall mechanical properties have been greatly reduced. Therefore, waste management of polymers should focus on regulating the relationship between the morphology of the substrate and the recombinant phase, which further proves the necessity of using compatibilizers during processing. At the same time, α-PP can also explain the poor impact strength of A0, and the impact performance of α-PP is not as good as that of β-PP. The specific size of the peak integrated area reflects the crystallinity to a certain extent, and the increase in crystallinity can also be confirmed by DSC analysis. It is speculated that carbon fiber or other filling components may nucleate in the form of impurities, thereby improving the crystallinity of R-PP.

[0053] As attached Figure 4 As shown, Figure 4 Thermodynamic analysis of the composites is shown, and it is possible to observe the single-step degradation processes experienced by the different components of the composites. Figure 4(a) is the TGA test, which shows that the actual initial decomposition temperature (tangent extrapolation point) increases when CF is added to the composite. The decomposition temperature of c4 increases from 450°C to about 458.2°C, indicating that the composite has better thermal stability than R-PP. After the addition of CF, the ablation performance gradually improves and reaches a peak at c4. The residual carbon mass fraction of A0 is 5.09wt.%, while the residual carbon mass fraction of C4 at 800°C is 10.07wt.%. This means that it has a significant improvement (about 97.84%) compared with the R-PP matrix. At the same time, it shows that the composite material after MAH compatibilization has better carbonization ability than the polymer matrix. This also shows that the blend has a certain degree of self-carbonization ability and flame retardancy. Overall, the addition of CF makes an important contribution to improving the thermal stability of the blend. TGA experiments fully demonstrate that micron-sized CF has a positive significance even at low additive content. The important marker data of TGA and DTG related to A0 and C series are detailed in S2. Figure 4 (d) and (e) represent the first temperature rise curve and the first temperature drop curve of the C system, respectively. It represents the peak value of the basic TmR-PP, which is about 165 °C. It is found by calculation that with the addition of CF, the crystallinity of the composite material has been improved to a certain extent and shows a regular upward trend. The increase in crystallinity usually leads to an increase in rigidity, but also a decrease in toughness, because the crystallinity regulates the interchain arrangement of the composite material, resulting in movement along the restricted molecular chain and increasing its intermolecular force. The melting peak at 125 °C can be understood as the PE impurity peak, and similar results were also found in the work. The DSC data related to the A0 and C series are detailed in S3. Figure 4 (f) is the melting point and crystallization temperature of the composite material after high-temperature annealing and elimination of thermodynamic history. S4 reflects the secondary heating curve and related physical parameters after a0 and c5 return. Compared with the original room temperature crystallinity, the crystallinity has no obvious change. The crystal structure of R-PP is incomplete and usually has crystal defects. The growth process of the new crystal essentially depends on the adhesion of the carbon chain of the molten material to the surface formed continuously by the original crystal. This is because the arrangement of atoms may cause the area to deviate from the ideal crystal structure due to the influence of atomic thermal motion or other conditions during the actual crystal growth process. Even after adding micron-sized CF to the low filler, the overall melting point still maintains a downward trend, which is caused by the block defects in the matrix lattice caused by it. After the microscopic matter damages the unit cell, it further leads to pores or cracks, which will further affect the thermal conductivity between phases, resulting in uneven heating after heating of each component, mainly referring to uneven heat transfer and diffusion capabilities. After passing the multiphase point, the local state changes and becomes the melting core, which is the beginning of the melting process. However, the presence of multiphase components in the composite material broadens the melting limit area, which well verifies the change of the DSC curve in the figure.

[0054] As attached Figure 5 As shown, Figure 5 (a) represents the result of sample density. The main purpose of this experiment is to measure the basic physical properties of the mixture and provide reliable parameters for further mechanical and physical performance analysis. It can be seen that the density of the composite material is positively correlated with the volume fraction of the added CF. This may be due to the addition of the compatibilizer, which mainly improves the uniformity of the blend by improving the adhesion between the phases, thereby further increasing the density of the composite material. This shows that the R-PP / POE / CF blend in this experiment is a lightweight or relatively light composite material. The density of the material determines the upper limit of its specific range of use.

[0055] Figure 5 (b) The results show that as the POE content increases, the overall strength and modulus of the composite material decrease compared to R-PP, while the elongation at break increases to varying degrees. The material has a larger plastic deformation space before breaking. This usually means that it has better scalability. It should be pointed out that the intentionally designed or adjusted POE weight percentage has a significant effect on the mechanical properties of the composite system. Figure 5 (c) shows the flexural properties of the c series composites, see S2 for specific data. The main disadvantage of POE is that it significantly reduces the flexural strength of the composites. Compared with a0, the flexural strength of C1 decreased by about 65.89%. The addition of CF effectively improved the flexural strength, and it continued to increase with the increase of CF filling rate. The flexural strength of C5 is 53.92% higher than that of C1. CF has a good and effective effect in both strength and modulus. Figure 5 (d), (e) and (f) represent the impact strength of composite materials A, B and C, respectively. After the addition of CF, the impact strength of system A decreases rapidly with the gradual decrease of POE content. In system B, the impact strength decreases slightly after the addition of CF, but the decrease in impact strength between B1, B2, B4 and B5 is not significant. In system C, the impact strength increases by two times with the increase of CF. Compared with A0, it increases from 4.10MPa to 33.39MPa and finally to 46.96MPa (AVG), with a maximum increase of more than 1000%. The increase of CF will further improve the impact strength of the composite material. In systems A and B, the impact strength decreases with the addition of CF, among which the impact strength of system A decreases most significantly, while the impact resistance of the composite material in system C is further improved with the addition of CF. This is similar to stretching, and the overall effect of adding CF on the composite material at different POE contents is completely different.

[0056] It is preliminarily speculated that this is because when the POE value increases to a certain proportion, the lower limit of the support threshold is reached. At this point, CF begins to synergistically enhance the impact resistance of R-PP-based composites. Due to the deformation of the thermoplastic elastomer after stress concentration, a large amount of energy generated by the external impact is consumed, and microcracks are difficult to spread further after they occur. Ultimately, it leads to a doubling of the impact strength. Related research explains the intrinsic toughening mechanism of thermoplastic elastomers and their impact on improving PP performance.

[0057]

[0058] From the above, it can be seen that compared with other materials, the composite material has better impact strength.

[0059] As attached Figure 6 As shown, Figure 6 Scanning electron microscope images of A0, C1, and C5 fracture surfaces at different magnifications. Figure 6 (a) and (b) show that R-PP itself is a mixture, and the impurities may be closely related to the sources in different types of plastic products. The appearance of pores may be due to the weakly bound recycled components being recovered from the matrix. After the addition of PP-g-MAH, the gaps and crack lines between the multiphase spaces are further reduced, and the adhesion between the interfaces is significantly increased. As shown in Figure 6(d), C1 shows obvious tearing after being subjected to external force. This may be because the hard segment (physical cross-linking point) of POE limits the further separation of the R-PP substrate, resulting in no obvious voids and a torn morphology. Figure 6 (e) and (f) show the microstructure of C5 at 500x and 10,000x magnification. The carbon fibers on the fracture surface can be clearly observed. It can be seen that under low load conditions, the CFs dispersed in the composite matrix are arranged in the same direction, which is directly related to the further improvement of the impact strength of the C system. The above phenomenon observed in the electron microscope may be related to the mechanical properties results discussed above. A clear bonding structure is formed between CF, POE and R-PP, and the good compatibility between thermoplastic rubber and plastic is also reflected in the composite system. In addition, the addition of CF does not change the characteristics of local plastic deformation after impact, that is, no large-scale destructive deformation occurs, which may also be an effective manifestation of preventing crack propagation and energy dissipation. Through the joint analysis of SEM and mechanical strength results, it is speculated that POE mainly has an intrinsic toughening effect or an intrinsic toughening effect. After being impacted, it prevents the appearance of crack tips by deformation or silver wire. After the tip appears, the fiber material represented by CF further consumes the impact energy through interface peeling, thereby reducing the attenuation of the crack, further accelerating the speed of the mixture, and ultimately improving the impact resistance. At the same time, it is inferred that CF / POE plays a major role in internal and external toughening under low load, with POE playing a major role and CF playing a supporting role.

[0060] The strength loss of PP / POE composites was prevented or improved by adding CF. In order to avoid the aggregation of CF in the matrix, the chemical reaction between PP-g-MAH and the CF surface was used to achieve the dispersion of CF. At the same time, the van der Waals force between PP-g-MAH and the R-PP / POE alkyl chain was used to connect the CF and R-PP / POE matrix, achieving the homogenization of the CF / R-PP / POE composite and fully improving the overall mechanical and thermal properties of the composite.

[0061] From the above, it can be seen that carbon fiber reinforced polyolefin elastomer / recycled polypropylene composite (CF / POE / R-PP) was prepared by mechanical blending, and its mechanical properties were systematically studied, with the following results:

[0062] Improve flexural strength: The presence of CF effectively improves the flexural strength of POE / R-PP. Carbon fiber, as a reinforcing material, plays a reinforcing role in the composite material, making the composite material have better strength and stiffness under bending load.

[0063] Improve thermal stability: The addition of CF further improves the thermal stability of POE / R-PP. Carbon fiber has excellent thermal stability, which can enhance the stability of polymers in high temperature environments and help prevent thermal decomposition and failure of materials.

[0064] Improve notched impact strength: The presence of CF further improves the notched impact strength of POE / R-PP. The addition of carbon fiber improves the fracture toughness of the composite material, allowing the material to better absorb energy under impact load and improve the impact strength.

[0065] Formation of a stable and dispersed composite interface: Maleic anhydride grafted polypropylene (PP-g-MAH) combines with the CF surface and the fused alkyl chains in R-PP and POE to form a stable and dispersed composite interface. The formation of this interface helps to improve the reinforcement effect of CF and increase the bonding strength and force transmission effect between CF and the matrix material.

[0066] Improved heat resistance: The addition of 9wt.% carbon fiber successfully improved the heat resistance of the composite material. The high thermal stability and thermal conductivity of carbon fiber help improve the performance of the composite material in high temperature environments, making the material better able to resist thermal decomposition and oxidation.

[0067] Significantly improve impact strength: The composite toughening of POE and CF effectively improves the impact strength of the composite material, with a maximum increase of more than 1000%. The addition of carbon fiber enhances the material's impact resistance, making the composite material better able to resist fracture and damage when subjected to impact loads.

[0068] The embodiments of the present invention are provided for the purpose of illustration and description. Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a recycled polypropylene / polyolefin elastomer / carbon fiber composite material, characterized in that: The steps include: S1, shaking R-PP, POE, and CF; S2, mixing R-PP, POE and CF using a twin-screw extruder to ensure uniform mixing of the materials; S3, sending the mixed materials into a crusher for crushing and granulation to obtain granular materials; S4, placing the granular material in a vacuum dryer for drying to remove moisture from the material; S5, molding the dried granular material using a twin-screw injection molding machine; S6, after the injection molding is completed, the prepared composite material is placed at room temperature for 36 to 48 hours to eliminate internal stress.

2. The method for preparing the recycled polypropylene / polyolefin elastomer / carbon fiber composite material according to claim 1, characterized in that: In step S1, the temperature of R-PP, POE and CF is between 175°C and 180°C.

3. The method for preparing the recycled polypropylene / polyolefin elastomer / carbon fiber composite material according to claim 1, characterized in that: In the step S4, drying is performed at a temperature of 80° C. for 8 hours.

4. Use of the recycled polypropylene / polyolefin elastomer / carbon fiber composite material prepared according to the method according to any one of claims 1 to 3 in pipes and disposable water cups.

Citation Information

Patent Citations

  • Thermoplastic composite, method for preparing thermoplastic composite, and injection-molded product

    CA2965841A1

  • Rigidity and toughness balanced polypropylene composite material and preparation method thereof

    CN118834471A

  • PULVERULENT POLYOLEFIN THERMOPLASTIC composition HAVING ELASTIC PROPERTIES

    FR2742441A1

  • A process for manufacturing waste textile fiber reinforced polymer composites and composites produced therewith

    WO2023285891A1